The Laws and General Ordinances of the City of New Orleans: Together with the Acts of the Legislature, Decisions of the Supreme Court, and Constitutional Provisions Relating to the City Government: Revised and Digested, Pursuant to an Order of the Common Council, Section 635, 257 (Henry Jefferson Leovy, Simmons & Co. New Ed. 1870) - (:unkn) unknown (General Publisher, 1870)
No person shall fire or discharge any gun, pistol, fowling piece or fire-arms, within the limits of the city, or set fire to, or discharge any rocket, cracker, squib or serpent, or shall throw any lighted rocket, cracker, squib or serpent, within the limits of the city, without the license of the common council; Provided, that nothing herein contained shall apply to military reviews or to the lawful use of weapons in self defense.
--
Keywords: DISCHARGE